2006
DOI: 10.1063/1.2336300
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Ohmic mechanism for chlorine-treated p-type GaN using x-ray photoelectron spectroscopy

Abstract: To investigate the function and mechanism of oxidation, the surface of the chlorine-treated p-type GaN semiconductor was analyzed using x-ray photoelectron spectroscopy. The chlorinated surface treatment was performed by electrolyzing HCl chemical solution to generate HClO, which in turn could be used to oxidize the p-type GaN. The chlorinated surface treatment enhances the formation of GaOx on the GaN surface and removing GaOx layer from the surface thereafter leads to the creation of additional Ga vacancies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…In this study, we find that the binding energy of N-Ga bonds was 398.5 eV higher than the report value, 397.5 eV [13,20], due to the N-face surface of GaN:O with opposite polarization direction, leading to the higher upward surface band bending. According to the results shown in Fig.…”
Section: Resultscontrasting
confidence: 72%
“…In this study, we find that the binding energy of N-Ga bonds was 398.5 eV higher than the report value, 397.5 eV [13,20], due to the N-face surface of GaN:O with opposite polarization direction, leading to the higher upward surface band bending. According to the results shown in Fig.…”
Section: Resultscontrasting
confidence: 72%
“…A detailed study of the chlorine-treated p-type GaN was reported previously. 15 Because an interfacial insulating oxide with a thickness of 1-2 nm has a serious influence on the electrical performance of metal contact on GaN, 16 it is necessary to remove GaO x from the chlorinetreated p-type GaN surface using aqua regia. The removal of GaO x can also induce additional Ga vacancy.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to the deposition of the Ni/Au Schottky metals, the native oxide residing on the GaN surface was removed using a chlorination surface treatment, [13][14][15] wherein an aqueous solution of 1 HCl þ 10 H 2 O was used as the electrolytic solution. A 700-nm-thick undoped GaN buffer layer and a 100nm-thick undoped Al 0.2 Ga 0.8 N buffer layer were grown on cplane sapphire substrates and then a 300-nm-thick undoped GaN absorption layer was grown.…”
Section: Methodsmentioning
confidence: 99%
“…6,7 Further, ultraviolet radiation detection devices have attracted much attention in emerging civil and military applications, such as chemical analysis, biological analysis, flame sensors, space-based optical communications, emitter calibration, and astronomical studies. [11][12][13] Among them, the chlorination surface treatment was verified to be a promising technology for the reduction of the surface states by passivating the Ga dangling bonds and the N vacancies residing on the surface of GaN-based semiconductors. [8][9][10] Among them, not only do metal-semiconductor-metal photodetectors (MSM-PDs) exhibit an ultralow intrinsic capacitance, but the related fabrication processes are compatible with field-effect-transistor-based electronic devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation